Modeling and analysis of ultrawideband biconical antenna; Modern technique and technologies MTT' 2012 - Zorkaltseva M. Y. (Section VIII: Modern Physical Methods in Science, Engineering and Medicine, 2012)
Заглавие с титульного листа